Pengaruh Model Pembelajaran Cooperative Integrated Reading and Composition Terhadap Kemampuan Membaca Intensif Peserta Didik Kelas IV - Silvana Bayu; Rina Devianty; Aufa (INDO PUBLISHING, 2026)
This study aims to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model on the intensive reading ability of fourth grade students. This type of research is an experimental study with a Pre-test Post-test Nonequivalent Control Group Design. This design requires two classes, namely the experimental class and the control class. The population of this study was all fourth grade students of Muhammadiyah 36 Elementary School Medan, totaling 107 people. Based on the results of the study, the average value of students who used the Cooperative Integrated Reading and Composition learning model was higher than the average value of students without using the Cooperative Integrated Reading and Composition learning model, namely 83.64 compared to 71.14. Based on the study, the results of the hypothesis calculation using the t test (Paired Sample T Test) at a significance level of 0.05 obtained the sig. (2 tailed) value is 0.000 £ 0.05, so it can be said that Ha is accepted and H0 is rejected. The results of the data analysis can be concluded that there is a very significant difference between the pre-test and post-test, thus there is an influence of the Cooperative Integrated Reading and Composition (CIRC) learning model on the intensive reading ability of fourth grade students at SDS Muhammadiyah 36 Medan.